Teachers’ self-efficacy in using ICT towards teaching and learning in mitigating Covid 19 Post pandemic era in Turkana central sub-county secondary schools (British Journal of Multidisciplinary and Advanced Studies, 2024)
ICT play roles towards achieving Kenyan educational goals through supporting teaching and learning. There was closure of schools following a directive from ministry of education. The pandemic affected teaching and learning in all schools paralyzing education sector. There was need carrying out a study investigating ICT implementation determinants in public schools in Turkana County in mitigating Covid 19. The purpose of the study was to investigate Teachers’ self-efficacy in using ICT towards teaching and learning in mitigating Covid 19 Post pandemic era in Turkana central sub-county secondary schools. Study objective was to investigate the Teachers’ self-efficacy in using ICT towards academic achievement. The study utilizes a conception framework showing relationships between variables. The study adopted Descriptive survey research design. The target were Secondary school teachers and learners from 20 schools. Saturated sampling was used to sample 20 head teachers and 20 teachers in public schools in Turkana County. Krejcie and Morgan (1970) sample table was used to select learners in checking their progress during the period of Covid 19 through simple random sampling. Data collection was done through questionnaires and interviews schedules. The experts from pedagogy area ascertained validity of the instruments. A pilot study comprising of 10 percent of schools to ascertain the instruments reliability. Data was analyzed through descriptive statistics that include tables, percentages. Findings revealed that the teachers agreed more, that portable ICT forms like iPad, tablets and phone helps their class stay organized and behaved in teaching and learning about COVID-19. ICT has not helped teachers and learners to attain attitude of self-confidence towards teaching and learning during post Covid -19. Furthermore, it has not helped manage situations confidently and effectively about teacher’s efficacy in classroom dynamics. The findings conclude that ICT affect the classroom dynamic in teaching and learning about COVID-19, Some do not use them appropriately for learning purpose, It lowers the class dynamics and participation, draws learners attention and Interference with other lessons. The study recommend that Teachers have to undergo extensive   ICT training to ensure effective use of the technology in class. The findings will help the ministry of education to improve on the appropriate use of ICT during any pandemic outbreak.